Changes in European energy markets : what the evidence tells us - Iovino, Felicetta; Tsitsianis, Nicholas (Bingley, U.K. : Emerald Publishing Limited, 2020)
Following the liberalization of EU energy markets, more than three hundred gas and electricity companies entered the market to substitute state-run monopolies. A sizeable shift has taken place within the European energy sector, one that remains only partially understood at best. Focusing on the financial performance of retail energy firms between 2008 and 2017, and taking the Italian market as its exemplara market that has arguably undergone the most significant transformation in EuropeChanges in European Energy Markets provides a critical and up-to-date analysis of this major development. Based on a comprehensive literature review and a wealth of data, the authors provide a compelling and much-needed account of the intensity and pace of change in the sector, which has been far from uniform. Changes in European Energy Markets is a must-read for students, researchers, practitioners and policymakers concerned with the seismic changes that have occurred within EU energy markets over the past decade.
Chapter 1: European energy markets: the liberalization processes -- Chapter 2: Italian energy markets: structure and functioning -- Chapter 3: The methodology of the research -- Chapter 4: The financial performance of energy companies: a review of literature -- Chapter 5: Analysis of the financial performance of the electricity and gas companies: empirical evidence from the Italian case.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Energy industries -- Europe; Energy industries -- Italy; Business & Economics -- Industries, Energy; Energy industries & utilities